The time course of semantic ambiguity in visual word recognition: behavioral and ERP evidence for the lexical-semantic effect - Kim, Joonwoo; Kim, Sangyub; Nam, Kichun (Frontiers in Psychology, 2024)
Homonyms are words that have multiple (and unrelated) meanings yet share a single form and pronunciation, thereby providing insight into how semantic representation is retrieved and selected independently of orthography and phonology. In this study, we investigated the temporal dynamics of lexical and semantic processing in the visual recognition of Korean words during a lexical decision task (LDT) with EEG recording. We compared the behavioral responses and event-related potentials (ERPs) evoked by homonyms and unambiguous words, each under conditions of either high or low word frequency. Both subjective and objective numbers of meanings (NOMs) were measured and manipulated while controlling for the subjective balance of individual frequencies of meanings to prevent potential confounding from the relatedness of meaning, namely the ROM effect. The behavioral results revealed a marginally significant interaction between word frequency and semantic ambiguity, along with a word frequency effect (i.e., faster and more accurate responses for high-frequency words). While a facilitatory effect (i.e., ambiguity advantage) was observed only for low-frequency words, no significant effect was found in high-frequency words. ERP results showed that this lexical-semantic interaction was reflected in modulations of the N400 and P600 components, concurrent with the word frequency effect. In the N400 time window, high-frequency homonyms elicited an enhanced amplitude, whereas a reduced P600 amplitude was observed for low-frequency homonyms. These findings suggest that the activation of semantic information occurs simultaneously with lexical processing, rather than during post-lexical or decision-making processes. Furthermore, considering balanced homonyms were employed in this study, inhibitory competition may arise from the high-frequency individual meanings of high-frequency words. In contrast, in low-frequency words, a facilitative effect may arise from gains in global semantic activation or semantic feedback to the orthographic level.